Pengaruh penggunaan bahan pewarna alam dari ekstrak kayu terhadap sifat fisis kulit ikan kakap merah - Emiliana Kasmudjiastuti; Widhiati Widhiati (Majalah Kulit, Karet, dan Plastik, 2002)
The objective of this research is to identify the effect of some natural dye of wood extract to the physical properties (tensile strength, elongation and rub fastness resistance) of kakap (Lutjanidae) fish skin leather. Fifteen pieces of dry preserved kakap fish skin were used in this research, and tanned using syntan and alum. The dyeing process was done using natural dyes of wood extract of Caesalpinia sappan L, Artocarpus heterophyllus, Swietenia mahagoni JACQ, Maclura cochinensis, and Ceriops tagal. The result of research indicated that the kind of applied natural dyes were not affect the physical properties of Kakap fish skins. The fish skins dyed using the such natural dyes was able be utilised as material in leather goods manufacturing. One of the five types of natural dye used in this research, Swietenia mahagoni JACQ wood extract produced the best dyed leather having good tensile strength, elongation/flexibility and the colour fastness. The tensile strength was 213,15 kg/cm2, flexibility 56% and colour fastness with wet white cloth 3/4 (grey scale value) and with dry white cloth 4/5 (grey scale value), respectively. Key words : kakap fish skin, natural dyes, physical properties.